A homozygous variant in TBPL2 was identified in women with oocyte maturation defects and infertility. Issue 7 (24th April 2021) - Yang, Ping; Chen, Tailai; Wu, Keliang; Hou, Zhenzhen; Zou, Yang; Li, Mei; Zhang, XinZe; Xu, Junting; Zhao, Han
Abstract: STUDY QUESTION: What are the genetic causes of oocyte maturation defects? SUMMARY ANSWER: A homozygous splicing variant (c.788 + 3A>G) in TATA-box binding protein like 2 ( TBPL2 ) was identified as a contributory genetic factor in oocyte maturation defects. WHAT IS KNOWN ALREADY: TBPL2, a vertebrate oocyte-specific general transcription factor, is essential for oocyte development. TBPL2 variants have not been studied in human oocyte maturation defects. STUDY DESIGN, SIZE, DURATION: Two infertile families characterized by oocyte maturation defects were recruited for whole-exome sequencing (WES). PARTICIPANTS/MATERIALS, SETTING, METHODS: Genomic DNA was extracted from peripheral blood for WES analysis. Sanger sequencing was performed for data validation. Pathogenicity of variants was predicted by in silico analysis. Minigene assay and single-oocyte RNA sequencing were performed to investigate the effects of the variant on mRNA integrity and oocyte transcriptome, respectively. MAIN RESULTS AND THE ROLE OF CHANCE: A homozygous splicing variant (c.788 + 3A>G) in TBPL2 was identified in two unrelated families characterized by oocyte maturation defects. Haplotype analysis indicated that the disease allele of Families 1 and 2 was independent. The variant disrupted the integrity of TBPL2 mRNA. Transcriptome sequencing of affected oocytes showed that vital genes for oocyte maturation and fertilization were widely and markedly downregulated, suggesting that a mutation in the transcriptional factor, TBPL2, led to global gene alterations in oocytes. LIMITATIONS, REASONS FOR CAUTION: Limitations include the lack of direct functional evidence. Owing to the scarcity of human oocyte samples, only two immature MI oocytes were obtained from the patients, and we could only investigate the effect of the mutation at the transcriptional level by high-throughput sequencing technology. No extra oocytes were obtained to assess the transcriptional activity of the mutant oocytes by immunofluorescence, or investigate the effects on the binding of TBPL2 caused by the mutation. WIDER IMPLICATIONS OF THE FINDINGS: Our findings highlight a critical role of TBPL2 in female reproduction and identify a homozygous splicing mutation in TBPL2 that might be related to defects in human oocyte maturation. This information will facilitate the genetic diagnosis of infertile individuals with repeated failures of IVF, providing a basis for genetic counseling. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the National Key Research and Development Program of China (2018YFC1004000, 2017YFC1001504 and 2017YFC1001600), the National Natural Science Foundation of China (81871168, 31900409 and 31871509), the Foundation for Distinguished Young Scholars of Shandong Province (JQ201816), the Innovative Research Team of High-Level Local Universities in Shanghai (SSMU-ZLCX20180401) and the Fundamental Research Funds of Shandong University. The authors have no competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.